2020
DOI: 10.1055/s-0040-1708480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Native Fucosylated Glycosaminoglycan, Its Depolymerized Derivatives on Intrinsic Factor Xase, Coagulation, Thrombosis, and Hemorrhagic Risk

Abstract: A native fucosylated glycosaminoglycan from sea cucumber Holothuria fuscopunctata (nHG), mainly branched with Fuc3S4S, exhibited potent anticoagulant activity by intrinsic tenase iXase (FIXa-FVIIIa complex) and antithrombin-dependent factor IIa (FIIa) inhibition, but also had the effects of FXII activation and platelet aggregation. For screening a selective iXase inhibitor, depolymerized nHG (dHG-1 ∼ –6) and a pure octasaccharide (oHG-8) were prepared. Like nHG, dHG-1 ∼ –6 and oHG-8 could potently inhibit iXas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 55 publications
3
39
0
Order By: Relevance
“…The main type of FucS branches in the native FG wasL -fucose-3,4-disulfates (Fuc 3S4S ), and the minor wereL -fucose-2,4-disulfates (Fuc 2S4S ) andL -fucose-4-sulfates (Fuc 4S ). The depolymerized fraction, dHG-5, was prepared from native FG by β-eliminative depolymerization as previously described (Zhou, Gao et al , 2020) and the high performance gel permeation chromatography (HPGPC) profiles of dHG-5 ( Figure 1A and Figure S2) showed that dHG-5 was the mixture of oligosaccharides with different degree of polymerization (dp). The molar percentages of the main oligosaccharides and those with dp > 29) in dHG-5 were estimated as 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main type of FucS branches in the native FG wasL -fucose-3,4-disulfates (Fuc 3S4S ), and the minor wereL -fucose-2,4-disulfates (Fuc 2S4S ) andL -fucose-4-sulfates (Fuc 4S ). The depolymerized fraction, dHG-5, was prepared from native FG by β-eliminative depolymerization as previously described (Zhou, Gao et al , 2020) and the high performance gel permeation chromatography (HPGPC) profiles of dHG-5 ( Figure 1A and Figure S2) showed that dHG-5 was the mixture of oligosaccharides with different degree of polymerization (dp). The molar percentages of the main oligosaccharides and those with dp > 29) in dHG-5 were estimated as 4.…”
Section: Resultsmentioning
confidence: 99%
“…Depolymerized FG (dFG) with average molecular weight (Mw) less than 12 kDa showed significantly improved selectivity of anti-iXase activity and had no obvious effects on platelets and f.XII (Kitazato, Kitazato et al , 1996;Wu, Wen et al , 2015). Among them, a 5.2 kDa-dFG fromHolothuria fuscopunctata (dHG-5) was developed in our group as a promising anticoagulant candidate, due to its advantages in mature preparation process, anti-iXase inhibitor selectivity, antithrombotic activity (Zhou, Gao et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the 1 H NMR spectrum (Figure 5A), five signals between 5.2 and 5.6 ppm could be assigned to five α anomeric protons of fucose with distinct sulfation patterns [3,24], since their 3 J H1-H2 values (3.6-4.6 Hz) were in agreement with that of α-anomers. They could be identified as α anomers of 2,4-O-disulfated fucose (Fuc2S4S, type I), 2-O-monosulfated fucose (Fuc2S, type II), 3,4-O-disulfated fucose (Fuc3S4S, type III), 3-O-monosulfated fucose (Fuc3S, type IV), and 4-O-monosulfated fucose (Fuc4S, type V), respectively, according to previous reports [3,4,13,15].…”
Section: Chemical Structures and Compositions Of Scsmentioning
confidence: 97%
“…The elution solvent was 0.1 M NaCl. The flow rate was 0.5 mL/min, and the temperature of the column was 40 • C. For Mw calculation, the Shodex OH-pak SB-804 HQ column (8 mm × 300 mm) was calibrated by a series of fucosylated glycosaminoglycan fractions from H. fuscopunctata with Mw of 39.9, 27.8, 14.9, 8.24, 5.30 and 3.12 kDa, determined by a size-exclusion chromatography with multi-angle laser light scattering [36].…”
Section: General Procedures For Physicochemical Properties Determinationmentioning
confidence: 99%